Socialism as an Organic Democratic Form of Life: On Axel Honneth's Project of a Renewal of Socialism Based on Social Freedom. Issue 1 (2nd January 2021) - Repa, Luiz
ABSTRACT: The article addresses Axel Honneth's project of renewing the idea of ⁣⁣socialism based on the concept of social freedom. At first, it emphasises the historical and philosophical singularity of this project within the tradition of critical theory, and then the political potentials represented by the concept of social freedom, especially concerning the openness to several forms of social conflict and the possibility of democratising intimacy. The article argues, however, that Honneth's proposal to conceive a socialist society as an organic whole undermines rather than enhances the attempt to revitalise socialism as democracy. Aimed at the functions of social integration, the organistic conception of society seeks harmony between the different social spheres (personal relations, economic structures, and political public sphere), which entails the risk of neglecting the intrinsic link between politics and conflict.